Spontaneous Hemothorax by Pulmonary Arteriovenous Malformation during Pregnancy - Chuxiao Duan; Yunfei Mu; Yi Yang (The Thoracic & Cardiovascular Surgeon Reports, 2023)
Background: Pulmonary arteriovenous malformation (PAVM) is a rare vascular malformation that may cause hemothorax, especially during pregnancy.